Ricoeur and the Hermeneutics of Suspicion. - Scott-Baumann, Alison (Continuum studies in continental philosophy., 2009)
Paul Ricoeur (1913-2005) was one of the most prolific and influential French philosophers of the Twentieth Century. In his enormous corpus of work he engaged with literature, history, historiography, politics, theology and ethics, while debating ''truth'' and ethical solutions to life in the face of widespread and growing suspicion about whether such a search is either possible or worthwhile. In Ricoeur and the Hermeneutics of Suspicion, Alison Scott-Baumann takes a thematic approach that explores Ricoeur''s lifelong struggle to be both iconoclastic and yet hopeful, and avoid the slippery slop.